Precedence-setting tokens: Issues of classification and functional attribution - Elena N. Malyuga; Asya S. Akopova (Peoples' Friendship University of Russia (RUDN University), 2021)
The study identifies and classifies the criteria instrumented to categorise and analyse precedence-setting tokens as units of sociocultural experience expressed in language and encapsulating some primary knowledge transmitted in the process of national, cultural and global development of a community. The authors set out to define and describe the essence of precedence-setting tokens as linguoculturological and socially and culturally significant units and offer an explanation for their typological categorisation based on theoretical observations cumulated from available studies on the concept in question. The study uses typological analysis to distinguish significant, internally homogeneous, qualitatively different groups of examined objects characterised by type-forming features of varying nature, as well as the functional approach whereby the perspectives of both the speaker and the listener are considered systemically to describe the functional potential enabling fulfillment of their communicative needs and intentions. The study claims that considered as units of language and speech that perform a set of specific communicative functions, precedence-setting tokens carry an extensive applicative potential, which can be highlighted by examining their eight key functions - nominative, persuasive, aesthetic, expressive, evaluative, comic, euphemistic, and the function of identity assessment.